PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN INFORMASI KEUANGAN TERHADAP ABNORMAL RETURN - Anugrawati, Mirna Arsita; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of corporate social responsibility disclosure and financial information which is proxy by the accounting profit, operating cash flow, investment, funding, and return on equity and debt to equity ratio to the abnormal return. The samples are manufacturing companies which are listed in Indonesia Stock Exchange in 2009-2013 periods. Based on the result of multiple regressions analysis with the significance level is 5%, therefore this research shows that: 1)The Corporate Social Responsibility disclosure ,operating cash flo and debt to equity ratio variable significant and positive influence to the abnormal return. 2) The accounting profit, investment cash flow , funding cash flow and return on equity variable not have any significant influence to the abnormal return.Keywords: corporate social responsibility, informasi keuangan, abnormal return